ANALYSIS OF CRITICAL FACTORS AND ITS IMPACT ON STRATEGIC PLANNING AND PERFORMANCE IN TOURISM SECTOR - Abdullah, Alkhaliel Adeeb (The journal of contemporary issues in business and government, 2021)
Tourism is considered as a main source of revenue and job opportunity as it brings developments for the country also plays an important role in promoting the image and global insight of the destination country. The strategic planning in tourism will create numerous vacancies, presentation of the environment, stability of the economy and also the improved quality of life. Strategic performance assessment has become an important way for guaranteeing the proper function of work in different formations and organizations. There are four main strategic components of tourism development known as attraction, accessibility, amenities and ancillary services. Employees of hotel residencies, restaurants, travel agencies and private companies were considered as a population of this study. Descriptive research design and Survey method is used to collect the responses from 285 employees from working in Tourism organizations. Statistical analysis is carried out to determine the level of influence among the variables like demographic variables, tourism attractions, supporting factors, competitive factors, and destination management. The factors such as tourism program, cultural & historical heritage, events & festivals, hospitality, climate, shopping opportunities, hotel services and multicultural ambience had significant positive influence on strategic tourism planning.